2021
DOI: 10.1101/2021.01.29.428807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stem cell-specific protein TRIM71 inhibits maturation and activity of the pro-differentiation miRNA let-7 via two independent molecular mechanisms

Abstract: The stem cell-specific RNA-binding protein TRIM71/LIN-41 was the first identified target of the pro-differentiation and tumor suppressor miRNA let-7. TRIM71 has essential functions in embryonic development and a proposed oncogenic role in several cancer types, such as hepatocellular carcinoma. Here, we show that TRIM71 regulates let-7 expression and activity via two independent mechanisms. On the one hand, TRIM71 enhances pre-let-7 degradation through its direct interaction with LIN28 and TUT4, thereby inhibit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
(171 reference statements)
0
4
0
Order By: Relevance
“…The shared list of upregulated genes included well-known let-7 targets such as Hmga2, Arid3a, Igf2bp1, Ccnd2 and Trim71 itself (table S3) (Figure 3D), suggesting that in cochlear organoid culture TRIM71 may inhibit the expression or activity of mature let-7 miRNAs or both. Recent studies found that TRIM71 represses mature let-7 miRNA expression by binding LIN28A or LIN28B proteins and enhancing their inhibition of let-7 biogenesis (Torres Fernandez et al, 2021). Our pull-down experiments using HEK293T cells revealed that NHL or Coiled-Coil deficient TRIM71 proteins failed to bind LIN28B (Figure S3), which correlated with the inability of NHL or Coiled-Coil deficient TRIM71 to upregulate the expression of the let-7 target Hmga2 in cochlear organoids (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shared list of upregulated genes included well-known let-7 targets such as Hmga2, Arid3a, Igf2bp1, Ccnd2 and Trim71 itself (table S3) (Figure 3D), suggesting that in cochlear organoid culture TRIM71 may inhibit the expression or activity of mature let-7 miRNAs or both. Recent studies found that TRIM71 represses mature let-7 miRNA expression by binding LIN28A or LIN28B proteins and enhancing their inhibition of let-7 biogenesis (Torres Fernandez et al, 2021). Our pull-down experiments using HEK293T cells revealed that NHL or Coiled-Coil deficient TRIM71 proteins failed to bind LIN28B (Figure S3), which correlated with the inability of NHL or Coiled-Coil deficient TRIM71 to upregulate the expression of the let-7 target Hmga2 in cochlear organoids (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed that TRIM71 interferes with the expression and function of mature let-7 miRNAs through enhancing LIN28A and LIN28B-mediated repression of let-7 biogenesis (Torres Fernandez et al, 2021) and through limiting the expression of AGO2, an essential component of miRNA-mediated gene silencing (Liu et al, 2021). Indeed, our transcriptomic profiling revealed that many of the up-regulated genes that were shared between TRIM71 and LIN28B were known or predicted targets of let-7 -mediated gene silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new twist is that recent studies suggest that mammalian LIN-41/TRIM71 can inhibit the accumulation of let-7 microRNAs (Liu et al . 2021; Torres-Fernandez et al . 2021b), suggesting its involvement as a component of a bistable developmental switch.…”
Section: Introductionmentioning
confidence: 99%